2011
DOI: 10.1007/s00256-011-1298-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 18 F-FDG-PET and PET/CT in patients with Ewing sarcoma family tumours: a systematic review and a meta-analysis

Abstract: With regard to the staging and restaging of patients with ESFT, the sensitivity, specificity and accuracy of FDG-PET and PET/CT are high; the combination of FDG-PET or PET/CT with conventional imaging is a valuable tool for the staging and restaging of ESFT and has a relevant impact on the treatment strategy plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 18 publications
0
50
2
4
Order By: Relevance
“…ES cells also showed a higher GAPDH expression, with particular regard to the SK-N-MC cells, reflecting a higher glycolytic activity. In keeping with the in vitro high glucose consumption of ES cells, the sensitivity, specificity, and accuracy of FDG-PET in this tumor have relevant impacts on treatment [35]. Using this approach, we therefore concluded that ES cells develop a compensatory response to adverse local environment that facilitates tumor progression through the simultaneous activation of mitochondrial respiration and upregulation of glycolysis.…”
Section: Discussionmentioning
confidence: 87%
“…ES cells also showed a higher GAPDH expression, with particular regard to the SK-N-MC cells, reflecting a higher glycolytic activity. In keeping with the in vitro high glucose consumption of ES cells, the sensitivity, specificity, and accuracy of FDG-PET in this tumor have relevant impacts on treatment [35]. Using this approach, we therefore concluded that ES cells develop a compensatory response to adverse local environment that facilitates tumor progression through the simultaneous activation of mitochondrial respiration and upregulation of glycolysis.…”
Section: Discussionmentioning
confidence: 87%
“…PET/CT has very high sensitivity and specificity of 96% and 92%, respectively, for detecting EESs. 17 Similar to skeletal ESSs, EESs are 18 F-FDG-avid tumours ( Figure 2). The mean SUVmax of the primary tumours in our study was 7 (range, 3-11).…”
Section: Discussionmentioning
confidence: 99%
“…Específicamente, en familia Ewing y PNET la adición de imáge-nes híbridas con TC a las tradicionales con PET efectuado con FDG es importante (sensibilidad, especificidad y precisión de PET: 71%, 95% y 88%, vs híbrido: 87%, 97% y 94%, respectivamente; ambas metodologías tienen relevancia e impacto en la estrategia de tratamiento 15,17 . En sarcomas óseos, uno de los factores pronósticos más importantes es la respuesta a la terapia que puede ser medida como porcentaje de necrosis y se puede observar como hipometabolismo central 13 .…”
Section: Discussionunclassified